2000
DOI: 10.1081/ada-100100598
|View full text |Cite
|
Sign up to set email alerts
|

Anger Management Group Treatment for Cocaine Dependence: Preliminary Outcomes

Abstract: Cocaine abusers who fail to manage anger appropriately may have greater difficulty achieving and maintaining abstinence. We conducted a pilot study to examine an anger management group treatment in a sample of 59 men and 32 women with a diagnosis of cocaine dependence. Participants attended a 12-week anger management group treatment and background substance abuse treatment. Levels of anger, negative affect, and anger control were measured at baseline, weekly during treatment, and at 3-month posttreatment follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 8 publications
2
30
0
1
Order By: Relevance
“…Evidence in support of this illustrates that anger often precedes and predicts future substance misuse (Eftekhari, Turner, & Larimer, 2004;Kirby, Lamb, Iguchi, Husband, & Platt, 1995) and that anger has been shown to be associated with relapse to substance use after treatment (Litt, Cooney, & Morse, 2000). In response to such evidence, anger management is viewed as an important component of SUD treatment (Fernandez & Scott, 2009;Lin, Mack, Enright, Krahn, & Baskin, 2004;Reilly, Clark, Shopshire, Lewis, & Sorensen, 1994;Reilly & Shopshire, 2000). However, little is known regarding the correlates of anger among this group which may help to inform such treatments.…”
Section: Anger Among Individuals With Sudmentioning
confidence: 88%
See 1 more Smart Citation
“…Evidence in support of this illustrates that anger often precedes and predicts future substance misuse (Eftekhari, Turner, & Larimer, 2004;Kirby, Lamb, Iguchi, Husband, & Platt, 1995) and that anger has been shown to be associated with relapse to substance use after treatment (Litt, Cooney, & Morse, 2000). In response to such evidence, anger management is viewed as an important component of SUD treatment (Fernandez & Scott, 2009;Lin, Mack, Enright, Krahn, & Baskin, 2004;Reilly, Clark, Shopshire, Lewis, & Sorensen, 1994;Reilly & Shopshire, 2000). However, little is known regarding the correlates of anger among this group which may help to inform such treatments.…”
Section: Anger Among Individuals With Sudmentioning
confidence: 88%
“…Clinical studies have consistently demonstrated elevated levels of anger among individuals in treatment for a variety of substance use disorders (SUDs; Aharonovich, Nguyen, & Nunes, 2001;Grisso, Davis, Vesselinov, Appelbaum, & Monahan, 2000;Reilly & Shopshire, 2000). Substance users report higher levels of state and trait anger, are more likely to express anger towards others, and have less control of their anger compared to norms and community controls (Aharonovich et al, 2001;De Moja & Spielberger, 1997;Tivis, Parsons, & Nixon, 1998).…”
Section: Anger Among Individuals With Sudmentioning
confidence: 95%
“…Anger management interventions developed for substance-using populations may be particularly effective for low-income persistent pregnant smokers (González-Prendes, 2008;Reilly et al, 2000) and may be more likely to prevent relapse than treatments focused on depression alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the parent study (n = 125), participants were recruited in 10 cohorts and then randomized into either in-person (control) or CVT (experimental) anger management treatment 46 groups. The current study uses post-treatment data from the six cohorts that were conducted on the remote islands of Maui and the Big Island of Hawaii; therefore, the data from the cohorts conducted on Oahu were excluded.…”
Section: Participantsmentioning
confidence: 99%